CYCLICAL ABSENTEEISM AMONG PRIVATE SECTOR, PUBLIC SECTOR AND SELF‐EMPLOYED WORKERS. (1st March 2012) - Pfeifer, Christian
ABSTRACT: This research note analyzes differences in the number of absent working days and doctor visits and in their cyclicality between private sector, public sector and self‐employed workers. For this purpose, I used large‐scale German survey data for the years 1995 to 2007 to estimate random effects negative binomial (count data) models. The main findings are as follows. (i) Public sector workers have on average more absent working days than private sector and self‐employed workers. Self‐employed workers have fewer absent working days and doctor visits than dependent employed workers. (ii) The regional unemployment rate is on average negatively correlated with the number of absent working days among private and public sector workers as well as among self‐employed men. The correlations between regional unemployment rate and doctor visits are only significantly negative among private sector workers. Copyright © 2012 John Wiley & Sons, Ltd.